2017
DOI: 10.1016/j.jclinepi.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Retrospectively patient-reported pre-event health status showed strong association and agreement with contemporaneous reports

Abstract: Retrospective collection offers a means of assessing PROMs in unexpected emergency admissions. However, further research is needed to establish the best policy for their use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…There are three possible explanations. First, it may be that patients recall their prior QoL as worse than it was, although no such bias was detected in studies of elective surgery when retrospective and contemporary reports were compared 14 15. Second, it may be that patients’ baseline disease-specific QoL was already lowered due to the presence of subacute symptoms prior to their AMI, but were not at the clinical threshold that warranted medical attention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are three possible explanations. First, it may be that patients recall their prior QoL as worse than it was, although no such bias was detected in studies of elective surgery when retrospective and contemporary reports were compared 14 15. Second, it may be that patients’ baseline disease-specific QoL was already lowered due to the presence of subacute symptoms prior to their AMI, but were not at the clinical threshold that warranted medical attention.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the feasibility of employing PROMs in emergency NHS admissions, an exploratory feasibility study was conducted in patients admitted with ST-segment-elevation myocardial infarction (STEMI) 13. Success of recruiting patients soon after admission and of obtaining their recollected state of health prior to their admission to provide a baseline assessment has been reported 13–15…”
Section: Introductionmentioning
confidence: 99%
“…A recent literature review on the relationship between retrospective and contemporary health status reports found strong agreement when the recall period is short [ 5 ]. However, only six studies have been undertaken of which only one was conducted in the UK [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…That study found strong agreement between retrospective and contemporary disease-specific PROs and EQ-5D, with intra-class correlation coefficients of 0.8 for the disease-specific PROs (Oxford Hip Score and Oxford Knee Score), and 0.6 for the EQ-5D. 3,4 An alternative approach that has been suggested is to derive expected PRO scores from respondents to general population surveys. Nine of the ten studies that have compared retrospective and population PRO scores have been conducted with trauma patients.…”
Section: Introductionmentioning
confidence: 93%